Analysis of the treatment results of localized conventional radiotherapy for early- and advanced-stage cutaneous T-cell lymphoma refractory to other skin-directed therapies - Jaehyeon Park; Jong-Hun Kim; Jin Park; Sun Young Lee (Wolters Kluwer Medknow Publications, 2019)
Background: Radiotherapy treatment was used as a skin-directed therapy for early- and advanced-stage cutaneous T-cell lymphoma (CTCL) refractory to other skin-directed or systemic therapies. Materials and Methods: From January 1990 to January 2017, eight patients with CTCL were treated with local radiation therapy. The median age of these patients was 41 years, and the female-to-male ratio was 1:3. The average disease course was 9.2 years. The patients were classified as Stage Ia (three patients), Ib (one patient), IIb (three patients), and III (one patient). Five patients received electron radiotherapy, and three patients received electron and photon radiotherapy. The mean number of treated lesions was 5.2 (range, 2-14 lesions). A median dose of 46 Gy (range, 40-50 Gy) was used. Results: After radiotherapy, complete and partial remission of the irradiated lesion was observed in 81% and 19% of all treated lesions, respectively. The treatment response in the early stage of disease was statistically significant (P = 0.0427). Local relapse was observed in eight lesions (two lesions in the irradiation field and six lesions outside of the irradiation field) after complete remission. A significantly lower recurrence rate was observed in the early stages of the disease (P = 0.0373). Radiotherapy resulted in long-lasting remission with early-stage CTCL. In addition, radiotherapy helped manage symptoms (pain, itching, and hyperkeratosis) in patients with advanced-stage disease. Conclusion: Localized conventional radiotherapy is effective for the treatment of early- and advanced-stage CTCL that is refractory to other skin-directed or systemic therapies, and the treatment is not associated with severe complications.